SORPTION OF Co2+, Cu2+, Zn2+ and Mn2+ METAL IONS FROM AQUEOUS SOLUTIONS ON ANIONIC SURFACTANT-MODIFIED BENTONITE (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
The sorption of Co2+, Cu2+, Zn2+ and Mn2+ metal ions on anionic surfactantmodified bentonite was studied. The optimal conditions for the effective sorption of Co2+, Cu2+, Zn2+ and Mn2+ metal ions from aqueous solution were obtained. It was established that sorption of studied metal ions on anionic surfactantmodified bentonite occurs both by ion-exchanging and adsorption mechanisms.
Keywords: metal ions, sorption mechanism, surfactant-modified bentonite